Brucea javanica Oil Emulsion Promotes Autophagy in Ovarian Cancer Cells Through the miR-8485/LAMTOR3/mTOR/ATG13 Signaling Axis - Yihan Wang; Bocen Chen; Man Xiao; Xiaoli Wang; Yunhua Peng (Frontiers Media S.A., 2022)
Background: Ovarian cancer is a common malignant tumor of the female reproductive tract, with the highest mortality rate. At present, no effective approaches to improve the survival rate exist. B. javanica Oil Emulsion (BJOE), an extract from B. javanica (L.) Merr. [Simaroubaceae], exhibits antitumor effects and can increase the sensitivity of radiotherapy and chemotherapy in many types of cancers. MiR-8485, a discovered miRNA, has been shown to be involved in the occurrence and development of tumors. The purpose of this study was to investigate the effect of BJOE on the regulation of mammalian rapamycin target protein (mTOR) autophagy signal pathway and related autophagy factors on ovarian cancer cells through miR-8485.Methods: The main chemical constituents of BJOE were determined by UHPLC-MS/MS. Detection of miR-8485 expression in ovarian cancer cells treated with BJOE by quantitative reverse transcription polymerase chain reaction (qRT-PCR). CCK8 experiment and flow cytometry were used to observe the effects of BJOE and overexpression of miR-8485 on cell proliferation and apoptosis. Then, monodansylcadaverine (MDC) fluorescence staining was used to observe the changes of autophagy vesicles before and after the effect of BJOE and overexpressed miR-8485 on cancer cells. Next, the binding sites between miR8485 and mammalian rapamycin target protein activator 3 (LAMTOR3) were detected by double luciferase reporter assay. Furthermore, qRT-PCR and Western blot experiments were used to explore the changes of autophagy-related factors LAMTOR3, mTOR and autophagy-related 13 (ATG13), and microtubule associated protein 1 light chain 3 beta (LC3-Ⅱ) after BJOE and overexpression of miR-8485, in addition to autophagy inhibitor (3-MA) for rescue experiment verification.Results: The qRT-PCR results showed that the expression of miR-8485 increased after BJOE treatment in the SKOV3 cell. The CCK8 assay and flow cytometry analysis revealed that both BJOE and miR-8485 overexpression inhibited the proliferation and promoted the apoptosis of the SKOV3 cell. MDC fluorescence staining showed that BJOE and miR-8485 overexpression led to a significant increase in autophagy vesicles in the SKOV3 cell. Double luciferase reporter assay confirmed the existence of binding sites between miR8485 and LAMTOR3. The results of qRT-PCR and Western blot showed that BJOE and overexpressed miR-8485 downregulated the expression of LAMTOR3 and mTOR and up-regulated the expression of ATG13 and LC3-Ⅱ.Conclusion: 1) MiR-8485 may be the key factor of BJOE in promoting autophagy and apoptosis and inhibiting cell proliferation of ovarian cancer cells; 2) BJOE may play an antitumor role by regulating LAMTOR3/mTOR/ATG13 signaling axis through miR-8485 to promote autophagy in ovarian cancer cells.